Effectiveness of a progressive resistance exercise program for industrial workers during breaks on perceived fatigue control: a cluster randomized controlled trial - Hélio Gustavo Santos; Luciana Dias Chiavegato; Daniela Pereira Valentim; Rosimeire Simprini Padula (BMC, 2020)
Abstract Background There is strong evidence that physical exercise in the workplace is effective for reducing workers' musculoskeletal complaints. Studies with industrial workers and studies on progressive resistance exercises during breaks are scarce. Our aim was to evaluate the effects of a resistance exercise program on perceived fatigue control among industrial workers. Methods 204 employees from the dairy industry were allocated to two groups, the intervention group (IG) (n = 98) and the control group (CG) (n = 106). The primary outcome measures were perceived fatigue control and maximum muscle strength, measured through the Need for Recovery Scale and one-repetition maximum contraction (1-RM), respectively. Secondary outcome measures were musculoskeletal complaints, physical activity level, perceived risk factors, physical fitness (BMI, vital signs, and body fat percentage), and workers´ productivity. All outcomes were assessed at baseline and then again after 4 months. The IG performed resistance exercises using progressively greater loads while the CG performed general exercise using elastic bands. The exercise protocols were performed three times per week for 20 min. An intention-to-treat analysis was performed using the mixed linear model. Results were considered significant when p < 0.05. Results The IG did not show to be superior to the CG, although both groups improved perceived fatigue control and muscle strength after the resistance physical exercise program in the worplace. There was also no significant difference between the groups for musculoskeletal complaints and other secondary variables analyzed. However, both groups showed significant improvements between baseline and after 4 months of intervention for all evaluated outcomes (p < 0.05). Conclusion The implementation of a progressive resistance exercise program during work breaks for perceived fatigue control was no more effective than exercises using elastic bands. However, resistance exercises during work breaks presented better results on all measured outcomes regardless of the exercise protocol used. Trial registration U.S. National Institutes of Health, ClinicalTrials.gov Identifier: NCT02172053 . Registered 19 June 2014.